Haemato-Biochemical Alterations In Induced Chlorpyrifos Toxicity In Broiler Chickens (Applied Biological Research, 2015)
Effect of graded doses of chlorpyrifos on haemato-biochemical indices in  broiler chickens was investigated. A total of 72 broiler chickens, 3 week old,  were divided into four groups (I to IV) consisting of 18 birds each. Group I  served as control, whereas groups II, III and IV received 3.2, 1.6 and 0.6 mg  kg-1 B.W. chlorpyrifos in corn oil daily for 6 weeks. Blood samples were collected in sterile vials containing EDTA (@ 1 mg mL-1) as anticoagulant  for haematological studies and without anticoagulant for biochemical  parameters. Mean values of Hb, PCV, TEC, MCV, MCH, MCHC, TLC and  lymphocyte counts decreased significantly in all the treatment groups,  whereas platelet count increased significantly. Serum total protein, albumin and A:G ratio showed decrease, whereas serum ALT, AST, RBC acetyl cholinesterase and butryl-cholinesterase activities exhibited increase. The  study revealed that chlorpyriphos has haemotoxic, immune-toxic,  hepatotoxic, nephrotoxic and neurotoxic effects in broiler chickens.
Keywords: Broiler chicken; chlorpyrifos; hematology; serum biochemistry